ANALISIS KESIAPAN MANAJEMEN SEKOLAH DALAM IMPLEMENTASI PENGELOLAAN ARSIP DIGITAL (STUDI KASUS TK SWASTA DI KOTA MATARAM) - Alfiatmi Laelatunnufus; Lulu Il Muntaz; Siti Julaikha (Yayasan Nusantara Hasana Berdikari, 2026)
Digital transformation demands mature school management readiness to ensure the sustainability of administrative governance. This study aims to analyze school management readiness in implementing digital archive management at a private kindergarten in Mataram. Using a descriptive qualitative method with a case study design, data were collected through in-depth interviews, observation, and documentation involving the school principal and teaching staff. The results indicate that school management readiness is in an unsystematic transition phase. Managerially, there is a high leadership disposition or commitment to innovate, but it is not yet supported by adequate human resource technical competence in digital document management. Management infrastructure readiness remains low due to limited technological devices and budget constraints. Furthermore, the managerial aspects have not been formally institutionalized in written policies or Standard Operating Procedures (SOP). This study concludes that strengthening school management through continuous training, formalizing policies, and optimizing cloud-based technology are key to a successful transition toward accountable digital archiving.